Implementasi Pembiayaan Murabahah Bil Wakalah di PT. BPRS Bhakti Sumekar Cabang Pratama Ra’as Sumenep - Ahmad Hamdi; M. Rivqi Amin; Mursyid Mursyid (Program Studi Akuntansi Syari'ah Universitas Ibrahimy, 2023)
As an intermediary institution, Islamic financial institutions (LKS) collect funds from the public through savings (savings), then channel them back to the community in the form of working capital and investment financing. One of the most dominant distributions of this financing is using a murabahah bil wakalah contract. As is the case with the BPRS Bhakti Sumekar Branch Pratama Ra'as. This study aims to find out in depth how the implementation of the contract in the field. Murabaha financing is the most dominant fund distribution scheme in LKS. Because it has a smaller risk for banks compared to implementing mudharabah and musyarakah contracts. This qualitative research uses data obtained from primary and secondary sources. Data is collected by observation, interview, and document methods. Any data that the researcher managed to collect, analyzed and tested its validity using source and method triangulation methods. The resulting conclusion is that the application of murabahah bil wakalah financing at BPRS Bhakti Sumekar Pratama Ra'as Branch is carried out with two contracts, namely starting with the wakalah contract first, then continuing with the murabahah contract. It's just that these two contracts are not set forth in their respective evidence, but are united in one contract agreement. This adaptation was made due to the efficiency and effectiveness aspects of time due to the limited number of BPRS personnel to serve the large number of financing customers.